Mikropropagasi Talas Satoimo Colocasia esculenta (L.) Schott var. Antiquorum melalui Meristem Apikal - Mustika Tuwo; Elis Tambaru; Baharuddin Patandjengi (Jurnal Ilmu Alam dan Lingkungan, 2021)
Japanese taro (satoimo) is a functional food source belonging to the Araceae family. Satoimo seedling production is conventionally constrained by limited land and uncertain climate, so that production decreases. One of the efforts to increase the production of satoimo seedlings can be done through plant tissue culture (in vitro). Meristem culture is an in vitro culture technique that is capable of producing plants free of viruses, bacteria and fungi. MS medium is a plant basal medium still requires the addition of growth regulators for growth and development of explants. This study aims to obtain the optimum concentration of growth regulator BAP (6-benzylaminopurin) which is able to produce the best taro growth in the apical meristem culture of satoimo taro. Explant sterilization is carried out at the tip of the shoot that emerges from the tuber. Then washed with detergent under running tap water for ± 30 minutes, followed by sterilization in Laminar Air Flow (LAF). Shoot tip explants were sterilized with 5.25% sodium hypochlorite plus 3 drops of tween 20. Soaking time varied depending on the treatment and then planted on MS medium with various concentrations of BAP. The parameters observed were the percentage of contamination, survival rate of explants, percentage of explant mortality, number of shoots, number of leaves and shoot height. Observations were made for 8 weeks. The mean and standard deviation were calculated using Microsoft Office Excel computer software. The results showed that the BAP concentration of 0.5 ppm was the best concentration for shoot growth of shoots and leaves, while the BAP concentration of 1 ppm was the best concentration for shoot height in the satoimo taro plant.